A pilot randomised controlled trial of negative pressure wound therapy to treat grade III/IV pressure ulcers [ISRCTN69032034] - Ashby, Rebecca L (BioMed Central, 2012)
BACKGROUND: Negative pressure wound therapy (NPWT) is widely promoted as a treatment for full thickness wounds; however, there is a lack of high-quality research evidence regarding its clinical and cost effectiveness. A trial of NPWT for the treatment of grade III/IV pressure ulcers would be worthwhile but premature without assessing whether such a trial is feasible. The aim of this pilot randomised controlled trial was to assess the feasibility of conducting a future full trial of NPWT for the treatment of grade III and IV pressure ulcers and to pilot all aspects of the trial. METHODS: This was a two-centre (acute and community), pilot randomised controlled trial. Eligible participants were randomised to receive either NPWT or standard care (SC) (spun hydrocolloid, alginate or foam dressings). Outcome measures were time to healing of the reference pressure ulcer, recruitment rates, frequency of treatment visits, resources used and duration of follow-up. RESULTS: Three hundred and twelve patients were screened for eligibility into this trial over a 12-month recruitment period and 12/312 participants (3.8%) were randomised: 6 to NPWT and 6 to SC. Only one reference pressure ulcer healed (NPWT group) during follow-up (time to healing 79 days). The mean number of treatment visits per week was 3.1 (NPWT) and 5.7 (SC); 6/6 NPWT and 1/6 SC participants withdrew from their allocated trial treatment. The mean duration of follow-up was 3.8 (NPWT) and 5.0 (SC) months. CONCLUSIONS: This pilot trial yielded vital information for the planning of a future full study including projected recruitment rate, required duration of follow-up and extent of research nurse support required. Data were also used to inform the cost-effectiveness and value of information analyses, which were conducted alongside the pilot trial. TRIAL REGISTRATION: Current Controlled Trials ISRCTN69032034.